Effect of Organizational Commitment and Job Satisfaction on Employees Performance at Cibabat Hospital, Cimahi City West Java - Indira Santi Kertabudi (Universal Journal, 2022)
Good performance and employee’s professionalism hospital are required by society, but health care at hospital is considered not good. Studies show that employee’s performance at hospitals is not maximal. This study purpose is to determine and measure the effect of organizational commitment and job satisfaction on employee performance. The method used is quantitative approach with path analysis techniques. Total sample of 100 employees are selected from total 500 populations. The research results show that level of employee’s performance was not associated with organizational commitment, but organizational commitment relates to job satisfaction, which ultimately can improve employee performance. Therefore, it becomes important to increase job satisfaction of public organizations, especially Cibabat Hospital to improve employee’s performance.